La connexió textual: l'adversitat en el nivell textual - Cuenca, M. Josep (Caplletra. Revista Internacional de Filologia, 2015)
This paper is about text connexity: similarities and differences with connexity in the sentence level, the conjunctive expressions which mark it (text connectives) and their function in discourse. All these aspects are reviewed paying particular attention to adversative connectedness.